Organic chromium modifies the expression of orexin and glucose transporters of ovarian in heat-stressed laying hens - Ozdemir, O.; Tuzcu, M.; Şahin, Nurhan.; Orhan, C.; Tuzcu, Z.; Şahin, Kazım (C M B Assoc, 2017)
In this study, the effect of the supplemental organic chromium (Cr) forms on the expression of ovarian orexin(hypocretin), glucose transporters (GLUTs), heat shock proteins (HSPs) andnuclear factor-kappaB (NF-kappa B) were investigated in laying hens (HS). Laying hens (n= 1800; 16-wk-old; Lohmann LSLLite) were allocated to 6 random groups according to a 2 x 3 factorial trial scheme with two different environmental temperatures [Thermoneutral (TN groups; at either 22 +/- 2 degrees C 24 h/d) and heat stress (HS groups; at 34 +/- 2 degrees C for 8 h/d, 08: 00 to 17: 00 h, followed by 22 degrees C for 16 h for a period of 12 wks)], andhens reared under both environmental conditions were fed either a basal diet or the basal diet supplemented with 1.600 mg of chromium-picolinate (CrPic, 12.43% Cr) and 0.788 mg of chromium-histidinate (CrHis, 25.22% Cr) per kg of diet, delivering 200 mu g elemental Cr per kg diet. HS groups showed decreased levels of orexin and GLUTs(GLUT1, GLUT4), and increased NF kappa B, HSP60, HSP70 and HSP90 levels compared to the TN groups in ovarian tissue of hens (P < 0.0001 for all). However, dietary chromium supplementation (CrPic-CrHis) increasedorexin and GLUTs levels and significantly reduced the NF-kappa B and HSPs levels making them closer to those of thermoneutral group (P < 0.0001). In conclusion, CrPic and CrHis showed supported the relief and treatment of stress complications.
Keywords: Heat stress; Chromium; Ovary; Orexin; GLUTs; NF kappa B